Building Resilient Food Security Against Global Crisis: New Evidence From China - Zuanxu Chen; Marina Zhang; Rebecca Kechen Dong; Shengpeng Wang (Food and Energy Security)
ABSTRACT The existing literature addresses the importance of food system disruptions and the risk of the global food crisis. However, there is insufficient understanding of response strategies and their effectiveness evaluations. This study offers a comprehensive introduction to China's food security policies and evaluates their effectiveness in enhancing the nation's risk resistance capability. Utilizing the Entropy Weight Method (EWM) and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), we evaluated China's provincial food security resilience (FSR) from 2003 to 2020 and adopted the ArcGIS platform to map spatiotemporal trends. Our findings reveal significant improvements in FSR nationwide, with a notable average annual growth rate of 1%–5%. However, regional disparities persist, with higher resilience observed in eastern provinces compared to the west. The study emphasizes the effectiveness of China's food security policies, which have synergistically enhanced grain production, agricultural mechanization, and farmers’ economic conditions. The article offers policy recommendations aimed at bolstering China's FSR and challenges with global implications. Our study contributes to the broader discourse on global food security by offering a nuanced understanding of the effectiveness of policy interventions in a major agricultural economy.